Hubungan Manajemen Waktu dengan Self Regulated Learning pada Mahasiswa Program Studi Diploma Tiga Keperawatan Universitas Abulyatama - Rachma Tsanya; Syukriadi Syukriadi; Pasyamei Rembune Kala (Lembaga Pengembangan Kinerja Dosen, 2025)
At the higher education level, students are expected to develop independence in their learning process. One crucial aspect that influences the achievement of self-directed learning is the ability to manage time effectively. This study focuses on the relationship between time management and self-regulated learning among students of the Diploma Three in Nursing Program at Abulyatama University. The research employed a quantitative approach using a correlational design and a cross-sectional method. A total of 85 participants were selected through proportional random sampling from a population of 554 students. The instruments used were the Time Management Questionnaire (TMQ) with a Cronbach's Alpha reliability of 0.910, and the Motivated Strategies for Learning Questionnaire (MSLQ) with a Cronbach's Alpha of 0.909. Data collection took place within the Diploma Three in Nursing Program at Abulyatama University from April 26 to May 9, 2025.The results showed that the majority of students had a moderate level of time management, with 63 students (74.1%), and a high level with 22 students (25.9%). Meanwhile, the level of self-regulated learning among students was moderate in 59 students (69.4%) and high in 26 students (30.6%). Analysis using the Chi-Square test revealed a significant correlation between time management and self-regulated learning, as indicated by a p-value of 0.000 (p ≤ 0.05). These findings suggest that students who are skilled in time management are more likely to possess higher self-regulated learning abilities. It is hoped that the results of this study will enhance students' understanding of the importance of time management, thereby encouraging them to adopt a more structured, focused, and sustainable self-learning pattern. Time management skills are believed to be a foundational element in strengthening self-regulated learning in students’ academic activities.